SOIL SALINIZATION AND ITS IMPACT ON THE DEGRADATION OF AGRICULTURAL LANDSCAPES OF THE TALAS DISTRICT, KAZAKHSTAN - Zhassulan Smanov; Salavat Duisenbayev; Kanat Zulpykharov; Shakhislam Laiskhanov; Zhanarys Turymtayev; Zhenis Kozhayev; Emin Atasoy; Omirzhan Taukebayev (Zbornik Radova: Geografski institut "Jovan Cvijić")
As a consequence of global population growth and increasing demand for agricultural commodities, vast areas of cultivable land have been brought under cultivation, while natural ecosystems are being converted for agricultural use. This transformation has led to various forms of soil degradation, with excessive salinity emerging as a critical concern. Drought-prone ecosystems are particularly vulnerable to salinization processes, resulting in an annual reduction of arable land by approximately 1% to 2%. In the Kazakhstan, salt-affected soils account for approximately 43% of all agricultural land. The aim of this study is to assess the extent and spatial distribution of soil salinity in the Talas district of Kazakhstan and to identify the dominant chemical characteristics of soil salts across different land types. To achieve this, soil samples were collected from river valleys, desert pastures, irrigated lands, and sandy areas. The analysis focused on salinization processes, ion toxicity thresholds, and the chemical composition of soil salts. Results reveal that salt accumulation varies between the 30 cm and 80 cm soil layers in river valleys and desert pastures, whereas the highest concentrations are observed in the upper layers of irrigated soils. The greatest variation in average salt content by soil texture was ±0.81% in loamy soils and ±0.62% in silty loam soils. These findings highlight the urgent need for ecologically sound land management strategies to mitigate soil salinization, especially in irrigated areas. They also offer valuable insights for enhancing irrigation efficiency and preserving soil fertility in Talas and other comparable regions.